COMPARISON OF SHARES IN PT ALAMTRI RESOURCES INDONESIA AND PT BUKIT ASAM - Hary, Bryen Keene; Emily Yulnina Atama; Rozzaqiyah Nur Rosyidah; Anindya Putri Inaayah; Muhammad Zaky Adriel (IJESM Indonesian Journal of Economics and Strategic Management, 2025)
This study aims to analyze and compare the stock performance of PT Bukit Asam (PTBA) and PT Adaro Energy (ADRO). The research employs a quantitative approach, utilizing numerical data analysis to support decision-making. The indicators used include expected return and standard deviation as performance metrics for the two companies. The results indicate that the expected return for PTBA is and for PT Adaro is Additionally, the study highlights the deviation and standard deviation values for each company. Based on these findings, it is concluded that the company with the lowest expected return is .... This study provides valuable insights for assessing the risk and potential returns of investing in these two companies